Developing Students' Creative Abilities Through the Use of Interactive Gaming Technologies in Biology Lessons (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The cultivation of students’ creative abilities has emerged as a priority in contemporary science education, particularly in the context of biology. Despite the increasing integration of digital tools in pedagogical practice, there is a lack of empirical evidence regarding the specific impact of interactive gaming technologies on the development of creativity. This study examines the effectiveness of interactive educational games in enhancing creative thinking among secondary school students during biology instruction. A mixed-method research design was employed, incorporating quantitative pre- and post-assessments alongside qualitative observations and student feedback. Participants were divided into experimental and control groups, with the experimental cohort engaged in biology-focused gaming activities aimed at promoting imagination, problem-solving, and critical thinking. The results demonstrated statistically significant improvements in the creative performance of the experimental group relative to the control group. Enhanced levels of engagement, task originality, and the capacity to transfer biological knowledge to novel contexts were observed. These findings support the integration of interactive gaming technologies as a means to foster creativity in biology education and offer implications for the design of innovative, student-centered curricula.